МОРФОЛОГИЯ И ПЕРЕФОРМИРОВАНИЯ РУСЛА НА УСТЬ-АЛДАНСКОМ УЧАСТКЕ Р. ЛЕНЫ - Ермакова А.С.; Кирик О.М. (My University, 2006)
Calculations of the spread of backwaters and falls of the Lena (near the Aldan mouth) were fulfilled. The features of bed morphology resulted from the interaction between the main river and the tributary are described. The major characteristic of the Lena channel dynamics is the change of the most active arm of the river with its main stream every 15-25 years. This change depends on water balance of the Lena and the Aldan, forming the backwater condition or its absence. The ratio of levels and dates of flood peaks is of significant importance in this process.
Keywords: 551.4.435.11(282.251.3)